The Catechetical Dimension of Traditional Wisdom Tegi Ndeter Agu Ndetar As A Path to Peace Education - Habur, Agustinus Manfred; Jehata, Hubertus Aliansi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study explores the catechetical dimensions of tegi ndeter agu ndetar, an indigenous reconciliation ritual in Manggarai, Eastern Indonesia, and its contribution to peace education. This study used a qualitative descriptive narrative case study in Manggarai Regency, Flores Island, with data collected through observation, interviews, and documentation. Five key informants, including traditional elders, a Catholic catechist, and a cultural practitioner, provided insights into the symbolic, moral, and catechetical dimensions of the tegi ndeter agu ndetar ritual. Data were analyzed through reduction, display, and interpretation using peace education, culturally sustaining pedagogy, and transformative learning theories, supported by relevant previous studies. Interpreted through peace education, transformative learning, and inculturation catechesis, the findings show that reconciliation is taught as a lived practice, where paradox and ritual generate transformative learning and Gospel values are transmitted through cultural forms. The study contributes theoretically by expanding peace education beyond classrooms into embodied cultural practice, affirming the role of paradox in transformative pedagogy, and grounding inculturation catechesis in communal life. Practically, it highlights opportunities for catechists, educators, and peacebuilders to collaborate with cultural elders in fostering reconciliation as a living curriculum of peace. Ultimately, tegi ndeter agu ndetar demonstrate that indigenous wisdom and Christian catechesis can converge as a pathway to sustainable peace education. The significance of this study lies in its contribution to bridging indigenous traditions and Christian pedagogy, offering a model of culturally rooted peace education that can inspire both academic discourse and practical pastoral approaches in diverse cultural contexts.